PELATIHAN MENGGOSOK GIGI UNTUK MENINGKATKAN KEMAMPUAN BINA DIRI ANAK TUNAGRAHITA SEDANG DI SLB - ARUM AGUSTININGSIH, ADELIA (Jurnal Pendidikan Khusus, 2016)
ABSTRACTMid mentally retardation children were one of the special need children who had limitedness in doing daily activity in keeping self hygiene, one of them was enhancing self guide ability to mid mentally retardation children.This research purpose was to obtain the description of self guide ability of mid mentally retardation children who had undergone brushing teeth training in SLB Dharma Wanita Lebo Sidoarjo. This research was quantitative with pre-experiment i.e. one group pretest – posttest design, with six subjects of mid mentally retardation children. The data analysis used statistic non parametric with wilcoxon test.The research result indicated that there was enhancement of self guide ability through brushing teeth training to mid mentally retardation children in SLB Dharma Wanita Lebo Sidoarjo, it was suitable with the average value of pre-test i.e. 44,41 and the average value of post-test was 63,01. From the result of data analysis it could be concluded that the counting number of Z = 2,20. This number was then compared with critic value 5% Z table was 1,96. This proved that the value of Z counted > 1,96 which meant that Ha was accepted and Ho was refused. It meant brushing teeth training was effective in enhancing self guide ability to mid mentally retardation children in SLB Dharma Wanita Lebo Sidoarjo.Keywords: Self guide ability, brushing teeth, mid mentally retardation